When a new leader takes over : toward ethical turnarounds - Sims, Ronald R. (Contemporary human resource management., 2017)
When a New Leader takes Over: Toward Ethical Turnarounds takes a detailed look at the experiences of new leaders who are charged with turning an organization around following an ethical scandal. The challenges confronting new leaders who are tasked with restoring trust, rebuilding reputation, and turning around an organization following an ethical scandal are discussed along with specific actions taken by these leaders during the turnaround process. A main focus of the book is to offer insight into the difficult situations confronting new leaders at the beginning, during and after their turnaround experiences which means turning an unethical organizational culture into an ethical one. A number of examples of turnaround efforts that have taken place over the past two decades are included to provide the most comprehensive documentation of the ethical turnaround process.The book includes an in-depth look at what led to the unethical behavior by examining a number of real-world examples of ethical scandals from around the world. The book will provide an analysis of the various ethical scandals by focusing on concepts like unethical leadership, received wisdom, groupthink and moral silence, all of which contribute to the kind of organizational culture and unethical behavior one finds in organizations that experience ethical scandals. The book also discusses proactive leadership and its importance in implementing ethical turnarounds based on values-based leadership, employee involvement and ethics education. A main premise of this book is that new leaders can successfully create an organization environment to rebuild and institutionalize ethical behavior as part of the turnaround process and sustain ethical behavior beyond the turnaround.The book will be of interest to employees at all levels of an organization, business professionals and other practitioners and others who have an interest in organization change, transformation and ethical turnarounds.